Study on the dynamics of Fish Farmer Group (Pokdakan) in Bukit Pinang Village, Samarinda Ulu District, Samarinda City - Fauziah, Dewy; Haqiqiansyah, Gusti; Juliani, Juliani (Faculty of Fisheries and Marine Science, Mulawarman University, 2025)
The aim of the research, is to determine the profile of the Rejang Raya Lake fish cultivator group (Pokdakan), and to find out the level of dynamism of the Rejang Raya Lake fish cultivator group (Pokdakan). The sampling method used was the census method with the number of respondents taken as many as 10 respondents. The analytical method used is a Likert scale to determine the level of dynamics of the Rejang Raya Lake fish cultivator group for each indicator: group goals, group structure, group tension, group effectiveness, hidden intentions are in the high category. The level of dynamics of the Rejang Raya Lake Fish Cultivator Group (Pokdakan) cumulatively obtained a score of 79.90, which is at a high level in the range of 63-81 and can be interpreted that the level of dynamics of the group is at high criteria (already dynamic) or the management and members it's been going well.